PRESERVING CULTURAL VALUES THROUGH POCKET PARKS IN AN URBAN ENVIRONMENT: A NARRATIVE REVIEW - Patria, Abdullah Hasif; Mohd. Hussain , Mohd. Ramzi; Tukiman, Izawati (Journal of Surveying, Construction and Property, 2025)
Modern urban areas face difficulties maintaining their cultural values due to their rapid growth. The purpose of this review is to synthesize existing research on how the roles of pocket parks can contribute to preserving the cultural values within an urban environment. A thorough search of databases specializing in pocket parks and cultural values was conducted. This study employs a narrative review of scholarly publications to evaluate how pocket parks, which are small, accessible green spaces, contribute to preserving cultural values in urban environments. The findings reveal how pocket parks play a role in preserving cultural values such as identity and authenticity by providing a public space that can offer artistic value and cultural expression. Additionally, with the preservation of cultural values, these parks also reinforce the sense of belonging that further enhances equity through placemaking, which can honour diversity while maintaining the unique identity of the community. Compared to past research, this study presents thorough evidence of literature from a diverse viewpoint, highlighting the roles of pocket parks that are significant towards cultural preservation in an urban environment. The findings advocate for designing policies that leverage small-scale interventions to balance cultural preservation with equitable development in rapidly transforming cities.